The Influence of Industrial Noise on Lipid and Lipoprotein Levels in Workers of Erbil Textile Factory - Mahmoud, Tayfoor Jalil; Ahmed, Salar Adnan; Ahmed, Zaher Taher (Sulaimani Journal for Pure and Applied Sciences, 2008)
This study was conducted to evaluate the influence of occupational noise (sound stress) exposure on fasting serum lipid and lipoprotein levels [ serum total cholesterol (TC) ,Triglycerides(TGs) and lipoproteins profile : Very Low Density Lipoprotein(VLDL),Low Density Lipoprotein(LDL-C) and High Density Lipoprotein (HDL-C)] in Erbil textile factory workers .These workers are exposed to high ambient noise level which is generated by big machines used in the factory for more than six hours daily at a strength of 90 deci-Bel [dB] without using ear protectors . The date obtained indicate that under these conditions of chronic and high noise exposure levels there are a significant increase (P< 0.05) in the level of fasting serum (TC) , a non significant increase in the levels of fasting serum ( TGs ,VLDL and LDL-C) and a significant decrease (p< 0.05) in the level of fasting serum (HDL-C) .
Keywords: sound stress; lipid and lipoprotein profile